Proteinuria and Reduced Estimated Glomerular Filtration Rate are Independently Associated With Lower Cognitive Abilities in Apparently Healthy Community-Dwelling Elderly Men in Japan: A Cross-sectional Study - Akira Fujiyoshi; Katsuyuki Miura; Takayoshi Ohkubo; Naoko Miyagawa; Yoshino Saito; Itsuko Miyazawa; Akihiko Shiino; Aya Kadota; Sayaka Kadowaki; Takashi Hisamatsu; Sayuki Torii; Naoyuki Takashima; et al. (Journal of Epidemiology, 2020)
Background: The association of proteinuria and reduced estimated glomerular filtration rate (eGFR) with cognition needs more clarification. We cross-sectionally examined whether proteinuria and reduced eGFR, even in moderate stages, were independently associated with lower cognition in a community-based sample of elderly men. Methods: Our cohort initially comprised 1,094 men aged 40–79 years from a random sample from Shiga, Japan in 2006–2008. Of 853 men who returned for the follow-up examination (2009–2014), we analyzed 561 who were ≥65 years, free of stroke, and completed the Cognitive Abilities Screening Instrument (CASI) at follow-up (higher CASI scores [range 0 to 100] indicate better cognition). Proteinuria was assessed via dipstick. eGFR was calculated according to the Chronic Kidney Disease Epidemiology Collaboration Equation. Participants were divided into three groups either by eGFR (≥60, 59–40, and <40 mL/min/1.73 m2) or by proteinuria (no, trace, and positive), considered normal, moderate, and advanced, respectively. Using linear regression, we computed mean CASI score, with simultaneous adjustment for proteinuria and eGFR in addition to other potential confounders. Results: Significant trends of lower cognition were observed across the groups of worse proteinuria and lower eGFR independently: multivariable-adjusted mean CASI scores were 90.1, 89.3, and 88.4 for proteinuria (Ptrend = 0.029), and 90.0, 88.5, and 88.5 for eGFR (Ptrend = 0.015) in mutual-adjustment model. Conclusions: Proteinuria and reduced eGFR, even in their moderate stages, were independently associated with lower cognition in a community-based sample of elderly men. The results suggest the importance of proteinuria and low eGFR for early detection and prevention of cognitive decline.